Concentraciones sanguíneas de sulfadoxina y pirimetamina según la respuesta terapéutica antimalárica, en dos municipios de Antioquia, Colombia (2005)
ABSTRACT: PROBLEM: There has been a constant increase in the level of therapeutic failure of the sulfadoxine-pyrimethamine (SP) combination for treating uncomplicated Plasmodium falciparum malaria. OBJECTIVE: To use high-performance liquid chromatography to quantify blood levels of SP in patients with good clinical response and in patients who did not respond to treatment. METHODS: This experimental study was carried out in 2002 in Turbo and Zaragoza, two municipalities in the department of Antioquia in Colombia. There were 79 patients (45 in Turbo and 34 in Zaragoza), including both men and women, who ranged in age from 1 year to 60 years. All the patients had uncomplicated Plasmodium falciparum malaria, with a parasite density of 500 to 50 000 parasites/L. The patients were each randomly assigned to a treatment group. The treatment groups were not blinded; the physician who provided the medication also evaluated the therapeutic response. The treatment consisted of a single combination dose of sulfadoxine (25 mg/kg) and pyrimethamine (1.25 mg/kg) in tablets (500 mg of sulfadoxine and 25 mg of pyrimethamine). Clinical-parasitological follow-up was carried out for 21 days. Blood levels of sulfadoxine and pyrimethamine were measured two hours after the treatment was given and also the day of treatment failure, if that occurred. RESULTS: Two hours after the treatment was given, the median blood level of sulfa-doxine was 136.6 µmol/L in the patients who later showed a good clinical response, and it was 103.4 mol/L among those who did not respond to treatment (P = 0.13). The medians for pyrimethamine were 848.4 nmol/L in patients with a good clinical response and 786.1 nmol/L in patients with treatment failure (P = 0.40). There were no significant differences in drug levels between the early-failure cases and the late-failure cases. The linear correlation between the blood levels of sulfadoxine and pyrimethamine was close to zero (r = 0.13). CONCLUSIONS: Between 1998 and 2002, treatment failure with the SP combination increased from 13% to 22% in Turbo, and from 9% to 26% in Zaragoza. The lack of response in 2002 could not be explained by lower blood levels of the medications.